Sensitivity Analysis and Accuracy of a CFD-TFM Approach to Bubbling Bed Using Pressure Drop Fluctuations - Tricomi, Leonardo; Melchiori, Tommaso; Chiaramonti, David; Boulet, Micaël; Lavoie, Jean Michel (Frontiers in Bioengineering and Biotechnology, 2017)
Simulations of fluidized bed (as in fluidized bed gasifiers) have always represented a challenge in chemical engineering, especially with regards to their complexity. Although not necessarily optimally adapted for biomass processing, such systems are already available on the market and it is of outmost importance to find economical approaches to optimise such reactors, especially when operating at large scale. Validation of CFD simulations for such systems has been so far possible using different sophisticated tools, allowing to link the model with experimental data. However, such high tech equipment may not always be available, especially at industrial scale. Hence, this article focuses on investigating the accuracy and numerical sensitivity of using the power spectrum distribution (PSD) to validate both a 2D and a 3D CFD models of a fluidized bed. Such tool, although it may look very simple, could help advances the fluidized bed technologies very fast and link CFD models closer to applications. Even though some studies went through pressure drop as a key output for validation purposes, the effect of the sampling time scale on the empirical data validity is lacking. Hence another aspect of this work focuses on the effect of this time scale on the empirical power-spectral density (PSD) which was investigated in order to achieve an optimal situation between simulation time requirement and consistency of the numerical validation with empirical data. The model was first numerically verified by mesh refinement process, after what it was used to investigate the sensitivity with regards to minimum fluidization velocity (as a calibration point for drag law), restitution coefficient and solid pressure term while assessing his accuracy in matching the empirical PSD.